Effects of Alpha-Connexin Carboxyl-Terminal Peptide (aCT1) and Bowman-Birk Protease Inhibitor (BBI) on Canine Oral Mucosal Melanoma (OMM) Cells - Sato, Ayami; da Fonseca, Ivone Izabel Mackowiak; Nagamine, Márcia Kazumi; de Toledo, Gabriela Fernandes; Olio, Rennan; Hernandez-Blazquez, Francisco Javier; Yano, Tomohiro; Yeh, Elizabeth Shinmay; Dagli, Maria Lucia Zaidan (Frontiers in Veterinary Science, 2021)
Abstract Oral mucosal melanomas (OMM) are aggressive cancers in dogs, and are good models for human OMM. Gap junctions are composed of connexin units, which may have altered expression patterns and/or subcellular localization in cancer cells. Cell-to-cell communication by gap junctions is often impaired in cancer cells, including in melanomas. Meanwhile, the upregulated expression of the gap junction protein connexin 43 (Cx43) inhibits melanoma progression. The α-connexin carboxyl-terminal (aCT1) peptide reportedly maintains Cx43 expression and cell-cell communication in human mammary cells and increases the communication activity through gap junctions in functional assays, therefore causing decreased cell proliferation. The Bowman-Birk protease inhibitor (BBI), a component of soybeans, induces Cx43 expression in several tumor cells as a trypsin–chymotrypsin inhibition function, with antineoplastic effects. This study investigated the effect of aCT1 peptide and BBI treatment, alone or in combination, on TLM1 canine melanoma cell viability. Cell viability after treatment with aCT1, the reverse sequence peptide (R-pep), and/or BBI for five days was analysed by PrestoBlue assay. Immunofluorescence was used to observe Cx43 localization and expression. aCT1 (200 μM) alone did not significantly decrease cell viability in TLM1 cells, whereas BBI (400 μg/mL) alone significantly decreased the TLM1 viability. Combined treatment with both aCT1 (200 μM) and BBI (400 μg/mL) significantly decreased cell viability in TLM1 cells. Cx43 expression, as identified by immunostainings in TLM1 cells, was increased in the cell membrane after the combination treatment with BBI and aCT1. This dual treatment can be combined to achieve the anticancer activity, possibly by increasing Cx 43 expression and affecting Cx43 migration to the cell membrane. In conclusion, a treatment strategy targeting Cx43 with BBI and aCT1 may possibly lead to new effective therapies for canine OMM.